The effect of nuclear status on morpho-physiological characteristics of the fungus Schizophyllum commune Fr. (Basidiomycetes) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Mycelium dikaryotic cultures of Sch. commune unlike monokariotic has almost twice the width of hyphae, formed colonies more dense with well-developed aerial and submerged mycelium are found. Electrophoretic studies endoenzymes systems allow us to identify dominant monokariotic culture with joint growth on the single substrate.
Keywords: Schizophyllum commune, monokariotic culture, dikaryotic culture, electrophoresis, isozymes, mycelium.